2015
DOI: 10.1515/ijafr-2015-0008
|View full text |Cite
|
Sign up to set email alerts
|

Mixing sweet cream buttermilk with whole milk to produce cream cheese

Abstract: Buttermilk is an important by-product of the manufacture of butter. Sweet-cream buttermilk (SCBM) is similar in composition to skim milk, except for its high phospholipid and milk fat globular membrane protein content. The main objective of this investigation was to produce optimum quality cream cheese by replacing whole milk with different proportions of SCBM (5, 10, 15, 20, 25, 30, 35, 40, 45, and 50%). Statistical analysis showed that there were significant differences (p < 0.05) between the chemical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 9 publications
3
22
2
Order By: Relevance
“…Similar range (17.1–19.8%) during the production of fresh cheese from buttermilk and milk mixes was obtained by Bahrami et al . (). These fluctuations may be caused by differences in the acidity and chemical composition of buttermilks.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Similar range (17.1–19.8%) during the production of fresh cheese from buttermilk and milk mixes was obtained by Bahrami et al . (). These fluctuations may be caused by differences in the acidity and chemical composition of buttermilks.…”
Section: Resultsmentioning
confidence: 97%
“…The lower content of fat in our study is explained by a substitution of full‐fat milk with low in fat buttermilk (Bahrami et al . ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The results showed that the best range for fortification using sweet‐cream buttermilk was 20−25% (Bahrami et al . ).…”
Section: Applications and Beneficial Health Characteristics Of Buttermentioning
confidence: 97%
“…The cream cheese manufactured by using 25 and 30% sweet-cream buttermilk had the highest yields. The results showed that the best range for fortification using sweet-cream buttermilk was 20À25% (Bahrami et al 2015).…”
Section: Applications Of Buttermilk In the Food Industrymentioning
confidence: 99%